2021
DOI: 10.1038/s41522-021-00231-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced stress-associated FKBP5 DNA methylation together with gut microbiota dysbiosis is linked with the progression of obese PCOS patients

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disease in females that is characterized by hyperandrogenemia, chronic anovulation, and polycystic ovaries. However, the exact etiology and pathogenesis of PCOS are still unknown. The aim of this study was to clarify the bacterial, stress status, and metabolic differences in the gut microbiomes of healthy individuals and patients with high body mass index (BMI) PCOS (PCOS-HB) and normal BMI PCOS (PCOS-LB), respectively. Here, we compared the gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 70 publications
0
33
1
Order By: Relevance
“…To address these challenges, we analyzed the microbial compositions and metabolic changes of fecal samples in the thiram-induced TD chicken model by combined 16S rRNA gene sequencing and UPLC/MS/MS-based metabolomics. Previous studies have confirmed that the analysis of these two methods is a well-established strategy for uncovering both gut microbial composition and functional features in various diseases ( Zheng et al, 2019 ; Kim et al, 2020 ; Wang et al, 2020 ; Chen et al, 2021 ). Therefore, based on this well-established strategy, we identified the microbial and metabolic signatures of TD in broilers to explore their reciprocal interactions in the gut ecosystem stability of TD.…”
Section: Introductionmentioning
confidence: 83%
“…To address these challenges, we analyzed the microbial compositions and metabolic changes of fecal samples in the thiram-induced TD chicken model by combined 16S rRNA gene sequencing and UPLC/MS/MS-based metabolomics. Previous studies have confirmed that the analysis of these two methods is a well-established strategy for uncovering both gut microbial composition and functional features in various diseases ( Zheng et al, 2019 ; Kim et al, 2020 ; Wang et al, 2020 ; Chen et al, 2021 ). Therefore, based on this well-established strategy, we identified the microbial and metabolic signatures of TD in broilers to explore their reciprocal interactions in the gut ecosystem stability of TD.…”
Section: Introductionmentioning
confidence: 83%
“…Özcan et al [526], Emokpae et al [527], Batista et al [528], Darbari et al [529], ElAlfy et al [530], Hounkpe et al [531], Vogel et al [532], Afifi et al [533], Shmukler et al [534], El Sissy et al [535], Cavalcante et al [536], Sadler et al [537], Kalai et al [538], Silva et al [539], Jhun et al [540] and Cai et al [541] that ALB (albumin), LPL (lipoprotein lipase), KL (klotho), UGT2B7, IFNG (interferon gamma), MPO (myeloperoxidase), BTK (Bruton tyrosine kinase), CD209, KCNN4, CCR5, TNF (tumor necrosis factor), CCR2, CCL5, NOS3, S100B and HBB (hemoglobin subunit beta) are associated with progression of sickle cell disease. Studies showed that altered expression of MTNR1A [542], GATA6 [543], EGF (epidermal growth factor) [544], LPL (lipoprotein lipase) [545], PPARGC1A [546], ERBB4 [547], KL (klotho) [548], GCLC (glutamate-cysteine ligase catalytic subunit) [549], NOX4 [550], SORCS1 [551], FKBP5 [552], CCNL1 [553], USP25 [554], SAA1 [555], MPO (myeloperoxidase) [556], GATA1 [557], LCN2 [558], IL1RN [559], IL11 [560], PDCD1 [561], TNF (tumor necrosis factor) [562], TNFRSF1B [563], APLNR (apelin receptor) [564], COMP (cartilage oligomeric matrix protein) [565], RETN (resistin) [566] and IGFBP1 [567] were associated with the progression of polycystic ovarian syndrome. Combined with the results of GO and REACTOME pathway enrichment analysis, these results imply these genes might participate in FSGS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mammadova et al suggested that gut microbiome of lean PCOS patients is similar with controls in bacterial richness and diversity [67]. However, Chen et al indicated that there are not significant differences between normal BMI PCOS and high BMI PCOS patients in bacterial diversity and community and they found the abnormal gut bacteria in PCOS maybe due to the bacterial response to stress which in turn leads to reduced stress-associated FK506binding protein 5 DNA methylation [68]. Accordingly, the abundance of bacteria in PCOS with IR are different from PCOS-alone and healthy patients [69].…”
Section: Microbiota Dysbiosis Of Pcosmentioning
confidence: 99%